2020
DOI: 10.1242/bio.056010
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments of tools for genome and metabolome studies in basidiomycete fungi and their application to natural product research

Abstract: Basidiomycota are a large and diverse phylum of fungi. They can make bioactive metabolites that are used or have inspired the synthesis of antibiotics and agrochemicals. Terpenoids are the most abundant class of natural products encountered in this taxon. Other natural product classes have been described, including polyketides, peptides, and indole alkaloids. The discovery and study of natural products made by basidiomycete fungi has so far been hampered by several factors, which include their slow growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 121 publications
0
17
0
Order By: Relevance
“…White-rot basidiomycete fungi are among the most powerful and efficient lignin degrading microorganisms known [50]. The development of genetic engineering tools for basidiomycetes -white-rot fungi being no exception -has traditionally been hampered by their long life-cycle, complex gene architecture, low efficiency of DNA fragment insertion into the chromosomes and protoplast production from spores [51,52]. Nevertheless, metabolic engineering efforts of white-rot fungi for lignin degradation have been undertaken giving promising results.…”
Section: Fungal Hostsmentioning
confidence: 99%
“…White-rot basidiomycete fungi are among the most powerful and efficient lignin degrading microorganisms known [50]. The development of genetic engineering tools for basidiomycetes -white-rot fungi being no exception -has traditionally been hampered by their long life-cycle, complex gene architecture, low efficiency of DNA fragment insertion into the chromosomes and protoplast production from spores [51,52]. Nevertheless, metabolic engineering efforts of white-rot fungi for lignin degradation have been undertaken giving promising results.…”
Section: Fungal Hostsmentioning
confidence: 99%
“…Bioactive compounds are organic molecules with normally small molecular weight that can be produced by both Ascomycetes and Basidiomycetes. Literature reports on fungal antiviral sources reveal that most known bioactive molecules have been isolated from Ascomycetes and Basidiomycetes, providing insights into the competence of those two phyla as producers of therapeutic compounds [ 45 48 ]. The studies indicated also that the biosynthetic gene clusters of the bioactive metabolites’ dominance are generally lower in number in basidiomycetes compared to the ascomycetes.…”
Section: The Potential Role Of Terpenoid Natural Products In Viral Infection Treatmentmentioning
confidence: 99%
“…H1N1and HSV-1 HSV-I Antiviral activity [43,44] two phyla as producers of therapeutic compounds [45][46][47][48].…”
Section: In Vitromentioning
confidence: 99%
“…Macrofungi are multicellular eukaryotes; most are binucleate or multinucleated cells. The low e ciency of obtaining homozygous mutations makes it di cult to achieve the speci c modi cation of target genes and multigene knockout or gene insertion mutations, thereby limiting basic research focused on macrofungi (Alberti et al 2020)…”
Section: Macrofungi and Other Fungimentioning
confidence: 99%